Combination of Pillow Use 30° and Sleeping Position on the Left Side Prevention Gastroesophageal Reflux based on Theory of Comfort: Study in Post-Egd Gerd Patients - Lya Marliana; Umdatus Soleha; Wesiana Heris Santy (Universitas STRADA Indonesia, 2025)
Background: Patients with suspected gastroesophageal reflux disease (GERD) often experience recurrent gastroesophageal reflux, where stomach contents repeatedly rise into the esophagus, causing disturbing symptoms. Purpose: Based on the results of the 2018 Riskesdas, the triggers for GERD were smoking prevalence in the population aged 10-18 years from 8.8% to 9.1% and the proportion of consumption of alcoholic drinks and types of alcoholic drinks in the population aged 10+ years from 3% to 3.3%. Comforting intervention is needed in nursing intervention by providing a combination of using a 30° pillow and left side sleeping position for GERD patients. According to Kolkaba, the level of comfort that can meet basic human needs is at the level of transcendence comfort. Methods: The method used is true experimental with a pretest-posttest control group design approach. This design involved two groups, namely the intervention group using a combination of using a 30°pillow and sleeping on the left side and the control group. Results: Data collection was carried out using questionnaires, direct observation and medical records. Conclusion: Based on the test results using Mann Whitney, a p value of 0.000 was obtained, where the value was <0.05, which means there was a difference in the gastroesophageal reflux score between the treatment and control groups in the delta/change data, where based on the mean value, the gastroesophageal reflux score for the treatment group had a decrease in score. Greater than the control group when delta/change data.